What can PrEP do for female sex workers? Unpacking the “effectosphere” of biomedical HIV prevention in Dar es Salaam - Lichtwarck, Hanne Ochieng; Massawe, Emmanuel Peter; Mmbaga, Elia John; Moen, Kåre (Social science & medicine (1982), 2024)
Pre-exposure prophylaxis (PrEP) is a drug with the power to prevent HIV transmission. This study delved into the broader implications of PrEP use among female sex workers in Dar es Salaam, Tanzania, a group disproportionately affected by HIV and socio-structural challenges. Through 46 in-depth interviews with 40 women who were either former or current PrEP users or intended to start PrEP between January 2021 and February 2022, we sought to explore the nuanced effects of PrEP. Inspired by Whyte et al. and “Social Life of Medicines”, we asked what PrEP could do in the lives of female sex workers and analyzed the data using reflexive thematic analysis and an interpretative phenomenological approach. We found that PrEP had multiple and diverse effects in many domains of women's lives and refer to these collectively as the “effectosphere” of PrEP. The study identifies four key themes that jointly describe this effectosphere: (1) PrEP could promote human flourishing and empowerment by facilitating a feeling of freedom and confidence which could promote health, social relations, and economic and work opportunities, (2) PrEP could inflict harm (and fears of such harms), partially reflecting medical mistrust rooted in an understanding that sex workers were undesired in society, (3) PrEP could expose sensitive information about its users that could lead to stigma, arguments and needs for elaborate explanations, and (4) PrEP could medicalize daily life, evidenced through daily pill taking, clinical appointments, side-effects, becoming reliant on the medication, and the challenges of integrating PrEP use with other life priorities. We argue that investigating the full effectosphere of any medicine in particular geographic and sociocultural contexts can lead to a better understanding of its use and non-use, highlighting that engaging with medication extends beyond just “taking a pill.” •PrEP is recommended for female sex workers in many contexts due to disproportionately high HIV risk.•This study asked how PrEP acted in the bodies and lives of female sex workers.•PrEP had multiple and diverse effects; referred to as the “effectosphere of PrEP”.•This included human flourishing, bodily harm, information exposure and medicalization.•The effectosphere can increase understanding of usage challenges and inform programs.